A Long‐term Analysis of Physician Triage Screening in the Emergency Department. (16th April 2013) - Rogg, Jonathan G.; White, Benjamin A.; Biddinger, Paul D.; Chang, Yuchiao; Brown, David F. M.; Pines, Jesse
Abstract Objectives The problem of emergency department (ED) crowding is well recognized; however, little data exist on the sustainability of potential solutions, including physician triage and screening. The authors hypothesized that a physician triage screening program (Supplemented Triage and Rapid Treatment [START]) sustainably improves standard ED performance metrics. Methods This retrospective, observational, before‐and‐after study compared performance measures over 4 years in a tertiary care urban academic medical center with approximately 90, 000 annual ED visits. Patients seen between December 2006 and November 2010 were included. Outcome measures included length of stay (LOS) for ED patients, percentage of patients who left without completing assessment (LWCA), percentage of patients treated and dispositioned by START without using monitored beds, and door‐to‐room time. Descriptive statistics were used. Results Median LOS for START patients was 56 minutes/patient lower when comparing 2010 to 2007 (p < 0.0001) and for non‐START patients 22 minutes/patient lower (p < 0.0001). The percentage of patients who LWCA decreased from 4.8% to 2.9% (p < 0.0001) during the same time period. In START's first half‐year, 18% of patients were discharged without using monitored beds. This increased to 29% by year 3. In addition, median door‐to‐room time decreased from 18.4 to 9.9 minutes during the same 3‐year interval. Conclusions Physician screening appears to provide sustainable improvements in ED performance metrics including ED LOS, percentage of patients who LWCA, door‐to‐room time, and percentage of patients treated without using a monitored bed, despite increasing ED volume. Physician screening delivers additional incremental benefits for several years after implementation and can effectively increase ED capacity by allowing emergency physicians to more efficiently use monitored beds.